The adolescent's perceptions and reasons for enjoyment at physical education classes in four elementary Brazilian schools - Vanilson Batista Lemes; Caroline Brand; Camila Felin Fochesatto; Adroaldo Cezar Araujo Gaya; Anelise Reis Gaya (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study aimed to describe adolescents' positive and negative perceptions and reasons for enjoyment in physical education (PE) in four schools, and to identify adolescents' opinions about possible improvements in PE classes. Material and Methods: This is a descriptive cross-sectional study, with a qualitative approach. The sample was composed of 240 girls and 230 boys, aged between 11 and 17 years according to exhaustion criteria, which is a requirement for the analyses of content. Perceptions and reasons for enjoyment in PE were evaluated according to three open questions. Analysis of content was applied. Results: There were different positive perceptions between schools related to sports enjoyment. Negative perceptions were mainly related to the teacher-student relationship, not having PE, and teachers' work methodologies. Suggestions were focused on diversifying specific physical activities, exercises, and sports. Conclusions: Adolescents enjoy PE due to fun, learning, liking physical activity practice, exercise, and sports. Negative perceptions were related to the difficulty with the teacher and not having PE classes. Adolescents suggest that they would like to have a wide variety of types of physical activity, physical exercise, and sport modalities.